Upregulation of ALOX12−12-HETE pathway impairs AMPK-dependent modulation of vascular metabolism in ApoE/LDLR−/− mice - Mariola Olkowicz; Agnieszka Karas; Piotr Berkowicz; Patrycja Kaczara; Agnieszka Jasztal; Zuzanna Kurylowicz; Filip Fedak; Hernando Rosales-Solano; Kanchan Sinha Roy; Agnieszka Kij; Elzbieta Buczek; Janusz Pawliszyn; et al. (Elsevier, 2024)
Mitochondrial dysfunction and 12-lipoxygenase (ALOX12)-derived 12(S)-HETE production have been associated with vascular inflammation and the pathogenesis of atherosclerosis. However, the role of ALOX12 in regulating vascular energy metabolism in vascular inflammation has not been studied to date. Using mitochondrial and glycolysis functional profiling with the Seahorse extracellular flux analyzer, metabolipidomics, and proteomic analysis (LC-MS/MS), we characterized alterations in vascular energy metabolism in 2- and 6-month-old ApoE/LDLR−/− vs. control C57BL/6 mice. We identified that aorta of 6-month-old ApoE/LDLR−/− mice displayed compromised mitochondrial metabolism manifested by the reduced expression of mitochondrial enzymes, impaired mitochondrial respiration, and consequently diminished respiratory reserve capacity. An increased flux through the glycolysis/lactate shuttle, the hexosamine biosynthetic pathway (HBP), and the pentose phosphate pathway (PPP) was also recognized. Interestingly, ALOX12−12-HETE was the most upregulated axis in eicosanoid metabolism and histological examinations indicated that ApoE/LDLR−/− mice showed increased aortic expression of ALOX12, particularly in early atherosclerotic plaque areas. Remarkably, the joint blocking of ALOX12 and activation of AMPK, but not AMPK activation alone, resulted in the reprogramming of vascular metabolism, with improved mitochondrial respiration and suppressed auxiliary pathways (HBP, PPP, itaconate shunt). In conclusion, excessive activation of the ALOX12-12-HETE pathway in vascular inflammation in early atherosclerosis inhibits AMPK-dependent regulation of vascular metabolism. Consequently, ALOX12 may represent a novel target to boost impaired vascular mitochondrial function in pro-atherosclerotic vascular inflammation.